Implementation of Deradicalization of Terrorism Convicts in Indonesia - Muhammad Safar; Yasmirah Mandasari Saragih; Muhammad Azhali Siregar; Sukardi Sukardi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The widespread movement of terrorism throughout the world is clear evidence that terrorist organizations are always developing and adapting to phenomena that occur globally. deradicalization is needed to neutralize the threat of terrorism from individuals who are motivated by religious ideology. In this writing, we will focus on the deradicalization of terrorism convicts in Indonesia. Radicalism is political ideas that are rooted and based on doctrines developed in opposition to the status quo . The deradicalization program in Indonesia consists of various approaches aimed at terrorism convicts. Terrorist groups continue to spread their radical beliefs through various means. Deradicalization as a form of special guidance for terrorism convicts is in accordance with the aim of the correctional system to return inmates to become good citizens so that they can be accepted back into society.